A 3-Year Review of Cranial Nerve Palsies from the University of Port Harcourt Teaching Hospital Eye Clinic, Nigeria - Pedro-Egbe, Chinyere Nnenne (Medknow Publications & Media Pvt Ltd, 2014)
PURPOSE: To provide the types, frequency and clinical information on common cranial nerve palsies seen at the Eye Clinic at the University of Port Harcourt Teaching Hospital. MATERIALS AND METHODS: A chart review was performed of patients who presented with cranial nerve palsy at the Eye Clinic over a 3-year period (January 2009-December 2011). Data were collected on age, sex, type of cranial nerve palsy, a history of systemic disease such as diabetes mellitus (DM), hypertension and cerebrovascular disease. Exclusion criteria included medical charts with incomplete data. Data was analyzed using Epi-info Version 6.04D. Statistical significance was indicated by P < 0.05. RESULTS: Twenty-four patients had cranial nerve palsies. There were 11 males and 13 females with a mean age of 34.50 ± 18.41 years. Four patients (26.6%) had exotropia while three patients (20%) had esotropia. Complete ophthalmoplegia was noted in two patients (13.3%). The 3(rd) and 6(th) cranial nerves were affected in seven patients each (29.2%) and five patients (20.8%) had 7(th) cranial nerve palsy. Approximately 38% of patients with cranial nerve palsies had systemic disorders (16.7% systemic hypertension; 12.5% DM). The relationship between cranial nerve palsy and systemic disorder was statistically significant (P < 0.01). CONCLUSION: This is the first study in the literature on ocular cranial nerve palsies in Southern Nigeria. Third and sixth cranial nerve palsies were the most common cases to present to the University of Port Harcourt Teaching Hospital Eye Clinic. There was a statistically significant association to systemic disorders such as hypertension and DM and majority of cases with 6(th) cranial nerve palsy.